2014
DOI: 10.1051/0004-6361/201424174
|View full text |Cite
|
Sign up to set email alerts
|

Determining the stellar masses of submillimetre galaxies: the critical importance of star formation histories

Abstract: Submillimetre (submm) galaxies are among the most rapidly star-forming and most massive high-redshift galaxies; thus, their properties provide important constraints on galaxy evolution models. However, there is still a debate about their stellar masses and their nature in the context of the general galaxy population. To test the reliability of their stellar mass determinations, we used a sample of simulated submm galaxies for which we created synthetic photometry. The photometry were used to derived their stel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 67 publications
6
90
0
Order By: Relevance
“…Consequently, it is not subject to the potential systematic errors that are associated with single-component SFHs (e.g. Michałowski et al 2012Michałowski et al , 2014. 3.…”
Section: Applicability Of the Results To Other Sed Modelling Codesmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, it is not subject to the potential systematic errors that are associated with single-component SFHs (e.g. Michałowski et al 2012Michałowski et al , 2014. 3.…”
Section: Applicability Of the Results To Other Sed Modelling Codesmentioning
confidence: 99%
“…Thus, it would be worthwhile to perform similar tests for other commonly used SED modelling codes. As a first step, Michałowski et al (2014) tested the ability of multiple SED modelling codes to recover the stellar masses of simulated submm galaxies (SMGs). They found that as long as a singlecomponent SFH was not used, all of the codes were able to accurately recover the stellar masses, albeit with a factor of ∼ 2 uncertainty.…”
Section: Applicability Of the Results To Other Sed Modelling Codesmentioning
confidence: 99%
See 3 more Smart Citations